RANCANG BANGUN APLIKASI PEMBELAJARAN TENSES BAHASA INGGRIS BERBASIS ANDROID PADA SEKOLAH MENENGAH PERTAMA NEGERI 3 SUKAMAJU - Rahmawati Rahmawati; Nirsal Nirsal; Syafriadi Syafriadi (Universitas Bina Bangsa, 2022)
This study aims to produce an Application for Learning English Tenses at The State Junior High School 3 Sukamaju so that it can make it easier for teachers and students. The data collection methods used in this study are observation, interviews, literature studies and documentation. In this study, the author used the R&D (Research and Development) method with reference to the waterfall model. System design using UML (Unified Modeling Language) as visual modeling, as for making applications using the MIT App Inventor platform to design applications. Tests performed on the system using black box testing. The results of this study are that the existence of an English tenses learning application system can make it easier for schools and students to carry out learning